2021
DOI: 10.3102/0091732x20985081
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Needs of All Cultureless Learners: Culture Discourse and Quality Assumptions in Personalized Learning Research

Abstract: This chapter reviews recent qualitative studies on personalized learning in middle/secondary school settings to analyze the role of culture in how this concept is enacted and researched. Personalized learning is posited as a pedagogical approach that aims to revolutionize schooling and challenge educational inequity by foregrounding learners’ agency in what and how they learn, tailoring pedagogy and its purpose to learners’ unique interests, needs, and abilities. Given the strong emphasis of the approach on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…In addition, Rusilowati and Wahyudi [47] demonstrated that teachers encountered difficulties in matching learning skills with inculcated cultural topics. Strekalova-Hughes et al [48] also explicated teachers' significant challenges in planning and implementing lessons related to students' cultures and backgrounds, due to insufficient knowledge and high reliance on the themes introduced in the textbook. Meanwhile, the study findings also assessed the issue of time allocation among teachers, as the classroom learning atmosphere must be related to effective planning and implementation when designing learning activities.…”
Section: Discussion 421 Contemporary Pedagogical Circumstancesmentioning
confidence: 99%
“…In addition, Rusilowati and Wahyudi [47] demonstrated that teachers encountered difficulties in matching learning skills with inculcated cultural topics. Strekalova-Hughes et al [48] also explicated teachers' significant challenges in planning and implementing lessons related to students' cultures and backgrounds, due to insufficient knowledge and high reliance on the themes introduced in the textbook. Meanwhile, the study findings also assessed the issue of time allocation among teachers, as the classroom learning atmosphere must be related to effective planning and implementation when designing learning activities.…”
Section: Discussion 421 Contemporary Pedagogical Circumstancesmentioning
confidence: 99%
“…AutoTutor uses natural language processing to model learners' cognitive and affective states and generate dialogue in a manner that adapts to these states (D'Mello et al, 2011). However, while existing personalized learning systems may consider social or emotional aspects of learning, the lens through which they are developed often assumes that these processes are universal and culture neutral (Roberts‐Mahoney et al, 2016; Strekalova‐Hughes et al, 2021). Past research has suggested that the way in which students purposefully engage with technology‐enabled personalized learning systems may not generalize well across cultural contexts (Rodrigo et al, 2013).…”
Section: Background Literaturementioning
confidence: 99%
“…The adaptive environment (Chatterjee, 2022) facilitates learners to self-regulate their learning and enable them to enhance their affective, psychological, cognitive and social development by learning to master their performance orientation and academic selfhandicap strategies. Their acceptance of the utility of technology should enhance their academic efficacy, personal achievement, goal orientation, academic-related perceptions, beliefs, and strategies (Roschelle & Burke, 2019;Strekalova-Hughes et al, 2021).…”
Section: Components Of Adaptive Learning Skillsmentioning
confidence: 99%